Blood Pressure Modifies Retinal Susceptibility to Intraocular Pressure Elevation - He, Zheng; Nguyen, Christine T. O.; Armitage, James A.; Vingrys, Algis J.; Bui, Bang V. (PLOS ONE, 2012)
Primary open angle glaucoma affects more than 67 million people. Elevated intraocular pressure (IOP) is a risk factor for glaucoma and may reduce nutrient availability by decreasing ocular perfusion pressure (OPP). An interaction between arterial blood pressure and IOP determines OPP; but the exact contribution that these factors have for retinal function is not fully understood. Here we sought to determine how acute modifications of arterial pressure will affect the susceptibility of neuronal function and blood flow to IOP challenge. Anaesthetized (ketamine:xylazine) Long-Evan rats with low (∼60 mmHg, sodium nitroprusside infusion), moderate (∼100 mmHg, saline), or high levels (∼160 mmHg, angiotensin II) of mean arterial pressure (MAP, n = 5–10 per group) were subjected to IOP challenge (10–120 mmHg, 5 mmHg steps every 3 minutes). Electroretinograms were measured at each IOP step to assess bipolar cell (b-wave) and inner retinal function (scotopic threshold response or STR). Ocular blood flow was measured using laser-Doppler flowmetry in groups with similar MAP level and the same IOP challenge protocol. Both b-wave and STR amplitudes decreased with IOP elevation. Retinal function was less susceptible to IOP challenge when MAP was high, whereas the converse was true for low MAP. Consistent with the effects on retinal function, higher IOP was needed to attenuated ocular blood flow in animals with higher MAP. The susceptibility of retinal function to IOP challenge can be ameliorated by acute high BP, and exacerbated by low BP. This is partially mediated by modifications in ocular blood flow.